Pengembangan Model Pelatihan Moral Politik Bagi Ormas PMKRI dengan Pendekatan Deduktif Berbasisikan Refleksi - Yohanes Vianey Sayangan (JTP - Jurnal Teknologi Pendidikan, 2015)
This Research and Development study designed to develop the suitable model for moral political training for students who join the PMKRI mass organization. In addition, use the combination of MPI Model and Gibs’ Re ection Model. The development stages of this research requires steps of system approach models of educational Research and Development. The formative evaluation activities put emphasis on the re ective approach designed in the training strategy and developed in the training material. In the end, this sort of material plays as the nal result of the model. Result, leads to the imperative categories for the PMKRI university students, developed a knowing, perceiving, and undertaking the essential moral political values.